Iron (II and III) Oxides/Reduced Graphene Oxide/Polypyrrole Ternary Nanocomposite as Electrochemical Supercapacitor Electrode. Issue 3 (30th March 2021) - Ghanbari, R.; Shabestari, M. Entezar; Kalali, E. Naderi; Hu, Y.; Ghorbani, S. R.
Abstract : In this work, ternary nanocomposites of iron (II and III) oxides/reduced graphene oxide/polypyrrole (iron oxide/rGO/PPy) have been prepared as the electrode materials of the supercapacitor. These nanocomposites were prepared via a facile two-step process including, the synthesis of iron oxides/rGO binary nanohybrids by a one-pot chemical-microwave method and in situ oxidative polymerization. The morphological and structural characterizations of these nanocomposites were demonstrated decoration of the iron oxides on GO sheets and proper formation of iron oxide/rGO/PPy ternary nanocomposites. The electrochemical performance evaluation of the samples revealed charge storage mechanisms in both the binary and ternary nanocomposites. A high specific capacitance of 626.8 F g −1 was obtained for the Fe2 O3 /rGO/PPy nanocomposite at a constant current density of 1 A g −1 in a 1 M H2 SO4 solution electrolyte. This high specific capacitance (vs 158.2 F g −1 for Fe3 O4 /rGO/PPy) can be assigned to the attendance of both electrical double-layer capacitance (EDLC) and pseudocapacitance mechanisms in its charge storage. The Fe2 O3 /rGO/PPy nanocomposite revealed the highest energy density of 87.05 Wh kg −1 with a corresponding power density of 500 W kg −1 . The frequency dependence and relaxation time constant investigation of these ternary nanocomposites revealed an ideal capacitive behavior at very low frequency and resistive behavior at the higher frequencies.